Perspectives on the Pure-Tone Audiogram - Musiek, Frank E.; Shinn, Jennifer; Chermak, Gail D.; Bamiou, Doris-Eva (Journal of the American Academy of Audiology, 2017)
The pure-tone audiogram, though fundamental to audiology, presents limitations, especially in the case of central auditory involvement. Advances in auditory neuroscience underscore the considerably larger role of the central auditory nervous system (CANS) in hearing and related disorders. Given the availability of behavioral audiological tests and electrophysiological procedures that can provide better insights as to the function of the various components of the auditory system, this perspective piece reviews the limitations of the pure-tone audiogram and notes some of the advantages of other tests and procedures used in tandem with the pure-tone threshold measurement.To review and synthesize the literature regarding the utility and limitations of the pure-tone audiogram in determining dysfunction of peripheral sensory and neural systems, as well as the CANS, and to identify other tests and procedures that can supplement pure-tone thresholds and provide enhanced diagnostic insight, especially regarding problems of the central auditory system.A systematic review and synthesis of the literature.The authors independently searched and reviewed literature (journal articles, book chapters) pertaining to the limitations of the pure-tone audiogram.The pure-tone audiogram provides information as to hearing sensitivity across a selected frequency range. Normal or near-normal pure-tone thresholds sometimes are observed despite cochlear damage. There are a surprising number of patients with acoustic neuromas who have essentially normal pure-tone thresholds. In cases of central deafness, depressed pure-tone thresholds may not accurately reflect the status of the peripheral auditory system. Listening difficulties are seen in the presence of normal pure-tone thresholds. Suprathreshold procedures and a variety of other tests can provide information regarding other and often more central functions of the auditory system.The audiogram is a primary tool for determining type, degree, and configuration of hearing loss; however, it provides the clinician with information regarding only hearing sensitivity, and no information about central auditory processing or the auditory processing of real-world signals (i.e., speech, music). The pure-tone audiogram offers limited insight into functional hearing and should be viewed only as a test of hearing sensitivity. Given the limitations of the pure-tone audiogram, a brief overview is provided of available behavioral tests and electrophysiological procedures that are sensitive to the function and integrity of the central auditory system, which provide better diagnostic and rehabilitative information to the clinician and patient.
Keywords: audiogram; auditory evoked potentials; central auditory processing disorder; diagnostic techniques